Best Answer

No. The Square root of x is not the value of x. So it can not be simplified beyond:

Root X + root 3x

Yes.

The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

Q: Can the square root of x be added to the square root of 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x^2 = 44 divide both sides by 3; x^2 == 44/3 x = +,- square root of 44/3 write 44 = 4 x 11; x = +,- 2(square root of 11/3) multiply the square root of 11/3 by square root of 3/3; x = +,- (2/3)(square root of 33)

√(3x - 5) = 3 ∴3x - 5 = 9 ∴3x = 14 ∴x = 14/3

4

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).The idea is to take any perfect square out of the square root sign. root(24) = root(4 x 6) = root(4) x root(6) = 2 x root(6).

Related questions

√(24x)4/√(3x) = [242x2√(3x)]/3x = 8(24)x√(3x) = 192x√(3x)

3x^2 = 44 divide both sides by 3; x^2 == 44/3 x = +,- square root of 44/3 write 44 = 4 x 11; x = +,- 2(square root of 11/3) multiply the square root of 11/3 by square root of 3/3; x = +,- (2/3)(square root of 33)

The question is ambiguous. Do you mean √(24*x4) or √24*x4? √(3x) or √3*x? The answer to √(24*x4) / √(3x) = (8x3) = 2x*√(2x)

√(3x - 5) = 3 ∴3x - 5 = 9 ∴3x = 14 ∴x = 14/3

If 2x2 + 3x + 9 = 0 then x = -0.75 - 1.984i or -0.75 + 1.984i where i is the imaginary square root of -1.

There is no sensible expansion of 3x + 4âˆš5

X^2 + 5 doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: 0 plus or minus i times the square root of 5.x = 0 + 2.23606797749979ix = 0 - 2.23606797749979iwhere i is the square root of negative one.

to find the inverse of a function you switch the x and y values, then solve for y. so y=(3x-7)^1/2 would change into x=(3y-7)^1/2. then you would square both sides to get rid of the square root and solve for y

Yes, because when x equals 1, the square root of x is rational and the square root of -x is irrational, and when x equals -1, the square root of x is irrational and the square root of -x is rational.

Simplified, It would be : 8+2r6x/8-3x (: r6 = the square root of 6.

By root, I'm going to assume you mean a square root. First, you try to isolate the root. Then, you simplify Then, you square everything (EVERYTHING). Set everything equal to zero. Then, you can solve for x using factoring. EX) √3x+2x+4=3x-2 Isolate your x. Therefore, √3x+2x=3x-2-4 √3x=3x-2x-2-4 Simplify. √3x=x-6 Square everything. (√3x)²=x²-6² Then, you get 3x=x²-36 Set it all = to zero. x²-3x-36=0 Now, you can factor. Factoring is a whole nother topic, it can be found on any website. Just google search "factoring". For this problem, you're gonna have to use the quadratic formula. Rather than do all that, I'm just going to say your answers- x=7.68465 x=-4.6846 You (normally) will have two answers when solving a sq rt problem, because in the last step, you end up with an (x+/-#)times(x+/-#)=0. You then set both of these parentheses equal to zero, so you have two answers.

The square root of the fifth root of x is the tenth root of x.